Minimally invasive management for multifocal pelvic retroperitoneal malignant paraganglioma: a neuropelveological approach - Giulia Zaccaria; Giuseppe Cucinella; Mariano Catello Di Donna; Giuseppe Lo Re; Giuseppe Paci; Antonio Simone Laganà; Vito Chiantera (BMC, 2022)
Abstract Background Pheochromocytoma and Paraganglioma (PGL) are rare neuroendocrine tumors, with an estimated incidence of about 0.6 cases per 100.000 person/year. Overall, 3-8% of them are malignant. These tumors are characterized by a classic triad of symptoms (headaches, palpitations, profuse sweating) due to hypersecretion of catecholamines. Despite several advantages of minimally invasive surgery (MIS) for PGL debulking, the surgical approach is not standardized yet. In this scenario, we aimed to report a case of a multiple recurrent PGL with metastatic retroperitoneal localization involving the pelvic sidewall, excised with MIS. Case presentation We performed complete laparoscopic-assisted neuronavigation (LANN technique) with isolation of the sacral routes and the sciatic nerve to obtain complete exposure of the main anatomic landmarks. Robotic surgery was used to perform neurolysis of sacral plexus, and partial resection of left splanchnic nerves was needed. After the resection of the first mass, extensive neurolysis of all sacral routes, obturator nerve, pudendal nerve till the entrance of the pudendal (Alcock) canal, and sciatic nerve was performed. Finally, the mass was identified after trans gluteal incision and dissection of the maximum gluteal muscle, and a partial resection of the superior gluteal nerve and slicing of the sciatic nerve were needed to obtain a radical excision of the mass. Then neurorrhaphy of the sectioned nerve fibers of the superior gluteal nerve was performed, and nerve protection was obtained using a collagen nerve wrap. After 18 months of follow-up, the patient is free of disease at the MRI imaging and 123I-metaiodobenzylguanidine scintigraphy. Conclusions Minimally invasive gynecological surgery with neuropelveological approach could be considered as a feasible option in case of multifocal pelvic retroperitoneal malignant paraganglioma of the pelvic side wall.